Climatic controls on debris‐flow activity and sediment aggradation: The Del Medio fan, NW Argentina. Issue 12 (20th December 2016) - Savi, Sara; Schildgen, Taylor F.; Tofelde, Stefanie; Wittmann, Hella; Scherler, Dirk; Mey, Jürgen; Alonso, Ricardo N.; Strecker, Manfred R.
Abstract: In the Central Andes, several studies on alluvial terraces and valley fills have linked sediment aggradation to periods of enhanced sediment supply. However, debate continues over whether tectonic or climatic factors are most important in triggering the enhanced supply. The Del Medio catchment in the Humahuaca Basin (Eastern Cordillera, NW Argentina) is located within a transition zone between subhumid and arid climates and hosts the only active debris‐flow fan within this intermontane valley. By combining 10 Be analyses of boulder and sediment samples within the Del Medio catchment, with regional morphometric measurements of nearby catchments, we identify the surface processes responsible for aggradation in the Del Medio fan and their likely triggers. We find that the fan surface has been shaped by debris flows and channel avulsions during the last 400 years. Among potential tectonic, climatic, and autogenic factors that might influence deposition, our analyses point to a combination of several favorable factors that drive aggradation. These are in particular the impact of occasional abundant rainfall on steep slopes in rock types prone to failure, located in a region characterized by relatively low rainfall amounts and limited transport capacity. These characteristics are primarily associated with the climatic transition zone between the humid foreland and the arid orogen interior, which creates an imbalance between sediment supply and sediment transfer. The conditions and processes that drive aggradation in the Del Medio catchment today may provide a modern analog for the conditions and processes that drove aggradation in other nearby tributaries in the past. Key Points: Present‐day aggradation in the Del Medio fan occurs within a transition zone between subhumid to arid climatic conditions Sediment supply is dominantly from landslides and rockfalls and transported by debris flows toward the Del Medio fan Aggradation in the Del Medio fan may provide a modern analog for past conditions that led to periodic aggradation in the Humahuaca Basin